2020
DOI: 10.3390/toxins12030165
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin-LR Does Not Alter Cell Survival and Intracellular Signaling in Human Bronchial Epithelial Cells

Abstract: Changes in ecological and environmental factors lead to an increased occurrence of cyanobacterial water blooms, while secondary metabolites-producing cyanobacteria pose a threat to both environmental and human health. Apart from oral and dermal exposure, humans may be exposed via inhalation and/or swallowing of contaminated water and aerosols. Although many studies deal with liver toxicity, less information about the effects in the respiratory system is available. We investigated the effects of a prevalent cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…Using in vitro expression systems, it was shown that the organic anion transporting polypeptides, specifically, OATP1B1, OATP1B3, OATP1A2, and Oatp1b2 are responsible for the uptake of microcystins and multidrug resistance-associated protein 2 (MRP2) is responsible for its efflux [ 58 , 59 , 60 ]. Interestingly, several cell lines that do not express these OATP variants have also exhibited microcystin uptake, suggesting that there are other microcystin uptake transporters that have not been identified [ 61 , 62 ]. The following section summarizes what is known regarding microcystin toxicokinetics and important gaps that remain to be addressed ( Figure 2 ).…”
Section: Microcystin Toxicokineticsmentioning
confidence: 99%
“…Using in vitro expression systems, it was shown that the organic anion transporting polypeptides, specifically, OATP1B1, OATP1B3, OATP1A2, and Oatp1b2 are responsible for the uptake of microcystins and multidrug resistance-associated protein 2 (MRP2) is responsible for its efflux [ 58 , 59 , 60 ]. Interestingly, several cell lines that do not express these OATP variants have also exhibited microcystin uptake, suggesting that there are other microcystin uptake transporters that have not been identified [ 61 , 62 ]. The following section summarizes what is known regarding microcystin toxicokinetics and important gaps that remain to be addressed ( Figure 2 ).…”
Section: Microcystin Toxicokineticsmentioning
confidence: 99%
“…Microcystins (MCs), one of the most common cyanotoxins, are produced by different genera of cyanobacteria and are considered to be a potent hepatotoxin with a wide range of effects [5,6]. They are cyclic heptapeptides, and most of them are hydrophilic due to carboxylic acids at positions 3 and 6, and to arginine, which is frequently found at positions 2 and 4 [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, structural modifications due to amino acid combinations can change the polarity of a peptide. MCs are a diverse group of toxins since variations in functional groups by methylation/demethylation, hydroxylation, and epimerization generate a wide variety of congeners; to date, more than 270 variants have been described [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…These cyanobacteria produce and release a large variety of biologically active secondary metabolites, cyanotoxins (Carmichael, 2001; Zhou, Tu, & Xu, 2015). Microcystins are an environmentally abundant large group of cyclic heptapeptide hepatotoxins (Brózman, Kubickova, & Pavel Babica Petra, 2020; Spoof et al, 2020). there are about 250 microcystin congeners varying primarily in amino acid constitution and degree of methylation (Spoof & Catherine, 2017) among which microcystin LR is widely studied variant (Brózman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Microcystins are an environmentally abundant large group of cyclic heptapeptide hepatotoxins (Brózman, Kubickova, & Pavel Babica Petra, 2020; Spoof et al, 2020). there are about 250 microcystin congeners varying primarily in amino acid constitution and degree of methylation (Spoof & Catherine, 2017) among which microcystin LR is widely studied variant (Brózman et al, 2020). Microcystin LR has been reported to accumulate in various organisms (Amorim & Vasconcelos, 1999; Greer, Meneely, & Elliott, 2018; Papadimitriou, Kagalou, Stalikas, Pilidis, & Leonardos, 2012; Prepas, Kotak, Campell, Evans, & Hrudey, 1997; Williams, Dawe, Kent, Andersen, & Craig, 1997; Xie, Xie, Guo, Miyabara, & Park, 2005) and produce a variety of effects, for example, hepatic damage (Kim et al, 2006; Srivastava & Srivastav, 2017), kidney (Dias et al, 2009; Shahi, Monalisa, Mallika, Sarmaa, & Dasa, 2012; Wang et al, 2019; Xiping et al, 2019), heart (Shahi et al, 2012), germ cell apoptosis (Zhao, Liu, Wang, Xu, & Xie, 2018) and human respiratory system (Brózman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%